2013
DOI: 10.1016/j.clinbiochem.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Significant, quantifiable differences exist between IgG subclass standards WHO67/97 and ERM-DA470k and can result in different interpretation of results

Abstract: We discuss the similarities and differences between assays that utilise the different reference materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
4
10
1
Order By: Relevance
“…As such, all other detected differences were due to classifications in neighboring categories. This might be in fact in contrast to Wilson et al . who reported up to 8.3% samples being categorized in opposite categories, while having otherwise very similar overall agreement scores of 87%‐95%.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…As such, all other detected differences were due to classifications in neighboring categories. This might be in fact in contrast to Wilson et al . who reported up to 8.3% samples being categorized in opposite categories, while having otherwise very similar overall agreement scores of 87%‐95%.…”
Section: Discussioncontrasting
confidence: 90%
“…The above described differences between the Siemens and the TBS IgGSc assay can be attributed to the fact that they are still calibrated to different reference materials . While the TBS IgGSc assay is calibrated to the serum protein reference material ERM‐DA470k/IFCC, the Siemens IgGSc assay is calibrated with the commercial standardization material Sanguin M1590 . Thus, even a decade after Bossuyt et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the standards used; the SPR and nephelometry analyses were performed with the ERM standard, whereas the ELISA analysis was made with the WHO67/97 standard. Running the ELISA standard in the SPR assay showed a decrease of the subclass concentrations (data not shown), confirming previous results on the two standards [16].…”
Section: Other Parameters Influencing Spr Assay Performancesupporting
confidence: 93%
“…Today, there are two different standards for plasma-derived IgG available: The Binding Site (TBS) Certified Reference Material 470 (now ERM-DA470k) [15] and Sanquin and Siemens WHO67/ 97 (now Sanquin M1590) [17]. There are reported differences in calibration and data interpretation between TBS and Sanquin IgGsc assays, especially for IgG3 and IgG4 assays, showing that the two manufacturers' assays could give different clinical classifications [3,16,18]. In the current study, the IgGsc analysis of IgG3 and IgG4 showed differences in ELISA analysis compared with SPR and nephelometry (Fig.…”
Section: Other Parameters Influencing Spr Assay Performancementioning
confidence: 95%
See 1 more Smart Citation